Concurrent strength and endurance training: Concepts and practical application in elite sports - Vogt, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Concurrent training for both strength and endurance is relevant in many sports. A prominent example is alpine skiing in which the mechanical and metabolic demands are very high during competition. Over the 45 to 150 seconds duration of a race, required power output is by far in excess of sustainable power levels in this sport. Hence there is a decline of muscle function, in particular a decrease of available muscle strength. It would thus seem that it is of advantage to have the capability of a very high initial power output combined with the metabolic capacity to maintain this power output as much as possible over the duration of the race. These requirements are in an important part related to maximal strength as well as oxidative capacity of muscle tissue. Methods: An overview on the physiological underpinning of modern alpine skiing will be given leading to a discussion on molecular mechanisms involved in the adaptive response to concurrent strength and endurance training. Considering this and according to the Docherty & Sporer`s interference model, concepts are developed with the aim to optimize the training process in elite alpine skiers in view of conflicting training goals. Results: From a molecular perspective there is evidence that the adaptive response of muscle to strength and endurance training is mediated by different signalling pathways. There is crosstalk between these pathways resulting in interference of adaptive signals with competing training stimuli. This can result in an interference and attenuation of the functional response to endurance and/or strength training. Manipulating training intensity in strength and endurance training is decisive to the degree by which central or peripheral (muscle) systems are affect by the stimuli. By this and/or by temporally separating strength from endurance sessions the interference effect can be diminished. Conclusion: Based on the molecular and functional insights as well as on practical experience it is concluded that training organization concepts like block periodization allows for efficient improvement of both strength and endurance in competitive alpine skiers.